Optimising Synchronisation Times for Mobile Devices - Lawrence, Neil D.; Rowstron, Ant; Bishop, Christopher; Taylor, Mike (Advances in Neural Information Processing Systems, 2001)
With the increasing number of users of mobile computing devices (e.g. personal digital assistants) and the advent of third generation mobile phones, wireless communications are becoming increasingly important. Many applications rely on the device maintaining a replica of a data-structure which is stored on a server, for example news databases, calendars and e-mail. In this paper we explore the question of the optimal strategy for synchronising such replicas. We utilise probabilistic models to represent how the data-structures evolve and to model user behaviour. We then formulate objective functions which can be minimised with respect to the synchronisation timings. We demonstrate, using two real world data-sets, that a user can obtain more up-to-date information using our approach.